Application of Taguchi method in optimizing the microstructure of 316LN austenitic stainless steel: Anwendung der Taguchi Methode zur Optimierung der Gefügestruktur des austenitischen Stahls X2CrNiMoN17‐11‐2. Issue 9 (14th September 2016) - Zhang, M. X.; Yang, B.; Wang, S. L.; Chen, Y. F.
Abstract : The hot deformation behavior of AISI 316LN austenitic stainless steel was studied through isothermal hot deformation tests conducted on Gleeble 1500 thermo‐simulation machine. By using Taguchi method with an L16 (4 3 ) orthogonal array, the hot deformation conditions including deformation temperature, strain rate and strain were optimized for obtaining minimum mean grain size of the steel. Analysis of variance was used for determining the effect of the hot deformation parameters on the mean grain size. The results suggested that the strain had the most significant effect on the mean grain size among the three factors. The percent contributions of deformation temperature, strain rate and strain to the mean grain size were 0.80 %, 2.45 % and 93.32 %, respectively. Finally, the confirmation experiment under the optimum conditions, i.e., 1050 °C temperature, 0.01 s –1 strain rate and 0.7 strain was carried out. The observational mean grain size (11.4 μm) is approximately twelve times smaller than that of the initial microstructure.